Researches in Cypriote History and Archaeology Proceedings of the Meeting held in Florence April 29-30th 2009 - Jasink, Anna Margherita; Bombardieri, Luca (Atti, 2010)
Researches in Cypriote History and Archaeology collects the Proceedings of an international meeting held in Florence in April 2009. The title and the contributions disclose how the original planning of a workshop in Florence evolved in time. A report of the University of Florence research activity in the Kouris river valley has been initially planned; as soon as the idea of the meeting was advertised, it was found appropriate to enlarge the horizon and to include in the discussion further issues on Cypriote History, Archaeology and Philology. It will, thus, be seen that starting from the Kouris Valley a kind of small overview on Bronze and Iron Age Cyprus has been put together. A wide variety of themes and interests raised up during the meeting in Florence, as well as a positive esprit de collaboration which allowed to share new results of interesting researches in progress, open further possibilities of exchanges and lead us to hope for a new meeting dedicated to Cypriote History and Archaeology, to be planned in Tuscany in a next future.